Damage initiation in composite materials under off-centre impact loading. (August 2018) - Nassir, NassierA.; Guan, Z.W.; Birch, R.S.; Cantwell, W.J.
Abstract: The effect of off-centre impact loading on damage initiation in a woven glass fibre reinforced epoxy resin was studied experimentally. Low velocity impact tests were conducted, in which the incident impact energy was increased until damage was observed in the laminates. It was shown that multiple impacts, with increasing incident energy at the same location, did not greatly influence the critical force for damage initiation, Pcrit . Subsequent testing on a range of panel sizes showed that the critical force is highest for central impacts, decreasing slowly as the impact location moves towards the boundary. It was also shown that, for off-centre impact loading, Pcrit, follows a t 3/2 (t = laminate thickness) relationship that has previously been established for central impact. The slope of the plot of Pcrit versus t 3/2 decreases as the impact location moves away from a central location, suggesting that the effective interlaminar shear stress also decreases with increasing offset. Tests at energies well above the damage threshold confirmed that off-centre impact is more serious than central impact loading. An energy-balance model was used to predict the off-centre impact response of the panels. Agreement between the energy-balance model and the measured impact response was good at energies that did not generate significant damage. Finally, it is suggested that the energy-balance model can also be used to predict a lower bound on the damage threshold energy in composite plates. Highlights: The effect of off-centre impact on damage initiation of woven glass fibre composites. Critical off-centre impact loading follows a thickness 3/2 relationship same as the central impact. Off-centre impact is more serious than central impact loading. Multiple impacts did not greatly influence the critical force for damage initiation. An energy-balance model is capable of predicting the off-centre impact response of the panels without significant damage.